Analisis Efektivitas Penggunaan System Console pharmacy terhadap Pembelian Obat Rawat Jalan Non Racikan di RS Premier Jatinegara - Pita Aprilia; Helen Andriani (Syntax Literate, 2023)
Hospital pharmacies are responsible for managing and monitoring the drug use process and ensuring the safe, effective, economical and timely availability of drugs to patients and hospital staff. The waiting times indikator set by the Hospital for non-compound drugs is less than 20 minutes with a target delay less than 10%. However, during the period July 2021 to June 2022, 56,77% of the drugs were prepared beyond 20 minutes. The Pharmacy Department and hospital manajemen decided to improve the manajemen of outpatient drug purchase queues by using an automated prescription queuing system (pharmacy console). Analyze the effect of using the console pharmacy system for outpatients purchase of non-compound drugs in terms of decreasing the percentage of delays when non- compound drugs are received by patients exceeding 20 minutes and increasing the number of line itemss in outpatient pharmacy. Analysis data of non-compound drugs delay report and the number of line itemss report in outpatient pharmacy in the period July-December 2022 after using the console pharmacy system. The number of prescriptions delayed more than 20 minutes decreased from a monthly average of 56.77% to 36.54%, a decrease of 20.23% per month. The number of Pharmacy line itemss also increased from the average per month in the previous period of 45,415 to 53,945 or an increase of 8,531 per month. Even though it still has not reached the target, the console pharmacy system has proven to be effective in providing many advantages for Premier Jatinegara Hospital in reducing waiting times and increasing the purchase of non-compound drugs in outpatients pharmacy. Pharmacy Departments and hospital manajemen must continue to work together for continuous improvement.